Empowering Teachers to Build a Better World How Six Nations Support Teachers for 21st Century Education - Reimers, Fernando M. (SpringerBriefs in Education, 2020)
This open access book presents a comparative study on how large-scale professional development programs for teachers are designed and implemented. Around the world, governments and educators are recognizing the need to educate students in a broad range of higher order cognitive skills and socio-emotional competencies, and providing effective opportunities for teachers to develop the expertise needed to teach these skills is a crucial aspect of effective implementation of curricula which include those goals. This study examines how large-scale efforts to empower teachers for deeper instruction have been designed, how they have been implemented, and their outcomes. To do so, it investigates six programs from England, Colombia, Mexico, India, and the United States. Though all six are intended to broaden and deepen students' curricular aspirations, each takes this expansion of curricular goals in a different direction. The ambitious education reforms studied here explicitly focus on building teachers' capacity to teach on a broader set of goals. Through a discerning analysis of program documents, evaluations, and interviews with senior leaders and participants in the programs, the book identifies the various theories of action used in these programs, examines how they were implemented, and discusses what they achieved. As such, it offers an indispensable resource for education leaders interested in designing and implementing professional development programs for teachers that are aligned with ambitious instructional goals.